INTERPRETASI POLA ALIRAN FLUIDA PANASBUMI MENGGUNAKAN METODE SPONTANEOUS-POTENTIAL (SP) DAN SUHU PERMUKAAN DANGKAL PADA SISTEM PANASBUMI PAGUYANGAN KABUPATEN BREBES - Yayan Yuliananto; Agus Setyawan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Fluid flow and temperature researchs has been done in Paguyangan geothermal manifestation based on spontaneous-potential and shallow surface temperature methods. An aims of research is to determine the pattern of fluid flow and shallow surface temperature distribution in the Paguyangan area, Brebes.Data acquisition for spontaneous potential measurement used fixed electrode configuration with 15 meters interval distance divided into 3 lines. Shallow surface temperature measurement which taken in 75 cm depth in around of Paguyangan manifestation area. Spontaneous potential anomaly and shallow surface temperature anomaly analyzed by correlated spontaneous potential, shallow surface temperature and rocks lithology in Paguyangan manifestation. The Result shows that spontaneous potential values obtained has range between -11 to 11 mV and temperature range between 24° to 70° C. Fluid flow has a depth range between 13,42 to 28,75 meters and range between 8,21 to 30,33 meters with a tilt range between 46,06° to 12,60°. The pattern of fluid flow leads to the northwest.Keywords: Spontaneous-Potential, shallow surface temperature, Pattern of fluid flow, Paguyangan